Effect of Gibberellic acid (GA3) on growth and production of tuberose (Polianthes tuberosa L.) - نصور, مازن; سلمان , يحيى; قدار, شيرين (Latakia University Journal -Biological Sciences Series, 2020)
This research aimed to study the effect of Gibberellic acid concentration (0, 100 and 200 p.p.m) and method of application (soaking, spraying and both) on growth, yield and quality of Tuberose. The experience included nine treatments repeated three times (30 plants by replicate). The results showed positive effect of GA3 on vegetative and floral characteristics, as well as tuber production . This effect varied according to GA3 concentration and method of application. Foliar spray was more effective than soaking in vegetative improvement particularly (GA3: 200 p.p.m). T6(100+200) and T7(200+100) soaking + spraying showed more effects than each alone, for vegetative growth (no. of shoots, no. of leaves, leaves area( Foliar spray with GA3(100 p.p.m) gave the best spike number and quality, and the highest proportion of essential oil. Spray with Low concentration of GA3 stimulated tuber production , while spray+ soaking with the same concentration increased tuber size.